2020
DOI: 10.1002/onco.13580
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Comparison of Molecular Tumor Boards in The Netherlands: Definition, Composition, Methods, and Targeted Therapy Recommendations

Abstract: Disclosures of potential conflicts of interest may be found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…However, these perspectives might change with new evidence: for example, there are promising novel agents and combination therapies currently under investigation that may be effective against EGFR exon 20 insertions, including amivantamab [ 79 ], poziotinib [ 80 ], and mobocertinib [ 81 ], or combining osimertinib or afatinib with cetuximab [ 82 ]. In the Netherlands, all Tier II and III EGFR variants are nowadays commonly discussed in Molecular Tumor Boards [ 83 ], resulting in favorable treatment outcomes [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these perspectives might change with new evidence: for example, there are promising novel agents and combination therapies currently under investigation that may be effective against EGFR exon 20 insertions, including amivantamab [ 79 ], poziotinib [ 80 ], and mobocertinib [ 81 ], or combining osimertinib or afatinib with cetuximab [ 82 ]. In the Netherlands, all Tier II and III EGFR variants are nowadays commonly discussed in Molecular Tumor Boards [ 83 ], resulting in favorable treatment outcomes [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, interdisciplinary solutions must be established to facilitate ongoing exchange between the various experts of precision medicine. Molecular tumor boards represent critical instruments for bringing together these decoupled knowledge domains to inform clinical decisions that ultimately benefit the patient and relieve healthcare systems [ 33 , 67 , 171 – 173 ]. Interestingly, although its importance is frequently emphasized at conferences and in other media [ 52 , 174 , 175 ], further education platforms for clinicians without access to MTBs are not prevalent, although young oncologists in particular would benefit immensely from learning about the fundamentals of genomics and liquid biopsy profiling early on in their training.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on Rotter’s 2010 Cochrane Review, the key dimensions identified for Patient Centered Care were communication [ 10 ], audit/feedback [ 11 ], informative systems [ 12 ], evidence-based application [ 13 ], multidisciplinary approach [ 14 ] and education sessions [ 11 ]. With regards to Personalized Medicine, on the other hand, the European Council’s document of 2015 identifies the molecular board [ 15 ], evidence-based genetic testing [ 16 ] and shared-clinical decision-making [ 17 ]. As such, eligible studies were those fulfilling t the definitions of patient-centered care and/or personalized medicine in terms of inclusion of the aforementioned dimensions.…”
Section: Methodsmentioning
confidence: 99%